A systematic review about the characteristics and patterns of use of outdoor gyms - Fernández-Rodríguez, E. F.; Merino-Marban, R.; Romero-Ramos, O.; López-Fernández, I. (Journal of Human Sport & Exercise, 2020)
The outdoor gyms have risen exponentially during the last years as a way of revitalizing public areas to enhance the practice of physical activity by insufficiently active older people. However, little is known about their use patterns that might help to maximize its benefits. To know the outdoor gyms profile, an exhaustive scientific literature review was made on research databases (WOS, Scopus, SportDiscus, CINAHL, Cochrane Library Plus, PubMed, Proquest Dissertations and Theses, and Google Scholar). Only 24 studies met the selection criteria of the 17,035 gathered. In general, outdoor gyms were used 3-5 days per week. They are 10-20 min away from users` home and distance was between 500 and 2007 m. Most activities on outdoor gyms were a supplement of other main PA. More rigorous study designs (intervention programs) are needed. It is necessary to operate in a community setting with local government. Current studies have indicated the existence of potential safety risks due to inappropriate usage behaviours. The most demanded improvements were more instructors, benches, variety devices, small roofs over the equipment, toilets, maintenance, lighting the area, security city guards, better promotion and placing information signs. The average number of devices per outdoor gym was 4,6. The dimensions were between 100-200 m2.